Fuzzy regression model with Bayesian approach and its application to public health data - Wan Ahmad, Wan Muhammad Amir bin; Nizam Akbar, Nurul Asyikin; Mohamad Ghazali, Farah Muna; Mohd Noor, Nor Farid; Aleng, Nor Azlida (Bulletin of Applied Mathematics and Mathematics Education, 2022)
The application of the Bayesian Linear Regression (BLR) and Fuzzy Bayesian Linear Regression method through the SAS algorithm is the focus of this paper. As an alternative method of data analysis in biostatistics, this modified method can be used. This modified method includes a bootstrapping technique, residual normality checking and some Bayesian Linear Regression Modeling (BLR) enhancement through Fuzzy Bayesian Linear Regression. We illustrated the application of the algorithm for Bayesian Linear Regression (BLR) and Fuzzy Bayesian Linear Regression in this paper.